2015
DOI: 10.1109/tmi.2015.2396774
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Segmentation of Vertebral Bodies and Processes Using Statistical Shape Decomposition and Conditional Models

Abstract: Abstract-Detailed segmentation of the vertebrae is an important pre-requisite in various applications of image-based spine assessment, surgery and biomechanical modeling. In particular, accurate segmentation of the processes is required for imageguided interventions, for example for optimal placement of bone grafts between the transverse processes. Furthermore, the geometry of the processes is now required in musculoskeletal models due to their interaction with the muscles and ligaments. In this paper, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
0
26
0
2
Order By: Relevance
“…The results reported by Korez et al and Castro‐Mateos et al were more accurate in the thoracic region but, to evaluate this region, they only included healthy patients. In addition, the development of completely automatic algorithms is still an open problem, being necessary in many cases some degree of user interaction . This has been accomplished with the current method, which is fully automatic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results reported by Korez et al and Castro‐Mateos et al were more accurate in the thoracic region but, to evaluate this region, they only included healthy patients. In addition, the development of completely automatic algorithms is still an open problem, being necessary in many cases some degree of user interaction . This has been accomplished with the current method, which is fully automatic.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the problems leading to back pain are related to lumbar region, as this area supports the greatest load of the spine. This is the reason why the majority of studies have only been focused on this region . Despite that, several studies found in the literature have made a great effort to segment all thoracic and lumbar vertebrae, but in most of the cases, the results obtained were more successful in segmenting the lumbar region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). To overcome these limitations, some researchers imposed statistical shape constraints on nonrigid registration [16, 25]. But it is difficult to implement them in practice due to pre-segmentation prerequisite and high complexity.
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…The use of atlas for aiding segmentation is an alternate method [14][15][16]. A three step algorithm is developed in [17] adopting Statistical Shape Models (SSM), that includes a seed placement, initial labeling and final optimization. This method is designed to handle complex geometry of all processes and variability between the individuals.…”
Section: Introductionmentioning
confidence: 99%